Noncontact plating technique in an open fracture - Tuhanioğlu Ü; Oğur HU; Çiçek H; Seyfettinoğlu F; Çiloğlu O; Kapukaya A (Dove Medical Press, 2017)
Ümit Tuhanioğlu, Hasan Ulaş Oğur, Hakan Çiçek, Fırat Seyfettinoğlu, Osman Çiloğlu, Ahmet Kapukaya Department of Orthopaedics and Traumatology, Adana Numune Training and Research Hospital, Adana, Turkey Aim: In comparison with closed fractures, open fractures have an increased risk of infection, there are soft tissue-related problems, and difficulties are experienced in union. The aim of this study was to evaluate and discuss the results of osteosynthesis applied with a noncontact plate in Gustilo–Anderson Type 2, 3a, and 3b fractures.Method: The study included 23 patients applied with debridement + noncontact plate osteosynthesis + soft tissue procedures in a single session for the treatment of an open fracture. A follow-up card was created to evaluate the patients in respect of age, gender, fracture level, fracture etiology, open fracture type, preoperative and postoperative sedimentation and C-reactive protein values, antibiotics used and duration of use, time to union, and complications.Results: In all 23 patients, full bone union was obtained at mean 22.5 weeks (range: 16–36 weeks). Complications developed in 9 patients. Implant failure occurred in 3 patients. In 5 patients, infection developed which required repeated debridements.Conclusion: In open fractures, noncontact plating following debridement seems to be a good alternative treatment method to intramedullar nailing, especially in metaphyseal and metaphyseo-diaphyseal fractures and in spiral oblique diafiz fractures. Noncontact plating may also be a good alternative to intramedullar nailing for open fracture treatment if the patients have additional pathologies such as contusion and thoracic injury. Keywords: plating, open fracture, infection